The Role of the North Bogor Police in Maintaining Harkamtibmas during the Rejection of the Construction of the Imam Ahmad Bin Hanbal Mosque - Rohmat Qodri (Tanggon Kosala, 2021)
It is been 4 years since the rejection of the construction of the Imam Ahmad bin Hanbal Mosque has not yet ended. North Bogor Polsek has an important role in efforts to prevent cases of intolerance between religious communities and the implementation of investigation, sambang, until patrol. This research aims to describe, analyze and identify the chronology, North Bogor Polsek roles as well as the factors the influence the rejection of the construction of the Imam Ahmad bin Hanbal Mosque. The research location is in North Bogor District with a focus on the role of North Bogor Polsek. This research uses the qualitative method with descriptive analysis techniques and field research. Using triangulation of primary data sources, secondary and tertiary, triangulation method and triangulation time by comparing data or information from interviews with observations in the field. This research uses iceberg theory, communication theory and social conflict based religion theory and role concept. This investigation, sambang and patrols were carried out by North Bogor Polsek which is not maximally analyzed from document study, interview and observations of police office especially to the public of Tanah Baru village. In carrying out research as well as sambang there are several pros and cons to factors that affect development rejection. The conclusion is that in the process of rejection of Imam Ahmad bin Hanbal Mosque development cannot be separated from the responsibility of the government and the police in guarding harkamtibmas in the community. It is been 4 years since the rejection of the construction of the Imam Ahmad bin Hanbal Mosque has not yet ended. North Bogor Polsek has an important role in efforts to prevent cases of intolerance between religious communities and the implementation of investigation, sambang, until patrol. This research aims to describe, analyze and identify the chronology, North Bogor Polsek roles as well as the factors the influence the rejection of the construction of the Imam Ahmad bin Hanbal Mosque. The research location is in North Bogor District with a focus on the role of North Bogor Polsek. This research uses the qualitative method with descriptive analysis techniques and field research. Using triangulation of primary data sources, secondary and tertiary, triangulation method and triangulation time by comparing data or information from interviews with observations in the field. This research uses iceberg theory, communication theory and social conflict based religion theory and role concept. This investigation, sambang and patrols were carried out by North Bogor Polsek which is not maximally analyzed from document study, interview and observations of police office especially to the public of Tanah Baru village. In carrying out research as well as sambang there are several pros and cons to factors that affect development rejection. The conclusion is that in the process of rejection of Imam Ahmad bin Hanbal Mosque development cannot be separated from the responsibility of the government and the police in guarding harkamtibmas in the community.